Consumers’ Willingness to Pay for Organic Products: A Case From Kathmandu Valley - Aryal, Kamal P.; Chaudhary, Pashupati; Pandit, Sangita; Sharma, Govinda (Journal of Agriculture and Environment, 2009)
This paper presents the consumers' willingness to pay a price premium for organic products in Kathmandu Valley. The Nepal Permaculture Group surveyed 180 consumers using semi-structured questionnaires to examine peoples' perception about organic products and assess their willingness to pay for such products. The study revealed that all respondents are willing to pay price premium, but the level of acceptability varied considerably. A total of 58% of the consumers are willing to pay 6- 20% price premium, whereas 13% are willing to pay up to 50% premium. The average premium was estimated about 30%. About 39% of the respondents feel the extra cost for organic products is reasonable, while 27% considered it too high. The survey also suggested that the consumption of organic products is increasing; however, product development and innovations in certification, processing, labeling and packaging are needed to further stimulate demand.  Key words: Certification; Consumer perception; Organic products; Price premium; Processing; Willingness to payThe Journal of Agriculture and Environment Vol:10, Jun.2009 Page: 15-26